A Berberine Bridge Enzyme-Like Protein, GmBBE-like43, Confers Soybean's Coordinated Adaptation to Aluminum Toxicity and Phosphorus Deficiency - Chen, Qianqian; Li, Jifu; Liu, Guoxuan; Lu, Xing; Chen, Kang; Tian, Jiang; Liang, Cuiyue (Frontiers in Plant Science, 2022)
Phosphorus (P) deficiency and aluminum (Al) toxicity often coexist and are two major limiting factors for crop production in acid soils. The purpose of this study was to characterize the function of GmBBE-like43, a berberine bridge enzyme-like protein-encoding gene, in soybean (Glycine max) adaptation to Al and low P stresses. Present quantitative real-time PCR (qRT-PCR) assays confirmed the phosphate (Pi)-starvation enhanced and Al-stress up-regulated expression pattern of GmBBE-like43 in soybean roots. Meanwhile, the expression of a GmBBE-like43-GFP chimera in both common bean hairy roots and tobacco leaves demonstrated its cell wall localization. Moreover, both transgenic Arabidopsis and soybean hairy roots revealed the function of GmBBE-like43 in promoting root growth under both Al and low P stresses. GmBBE-like43-overexpression also resulted in more H2O2 production on transgenic soybean hairy root surface with oligogalacturonides (OGs) application and antagonized the effects of Al on the expression of two SAUR-like genes. Taken together, our results suggest that GmBBE-like43 might be involved in the soybean's coordinated adaptation to Al toxicity and Pi starvation through modulation of OGs-oxidation in the cell wall.